First report of Neoscytalidium novaehollandiae associated with branch dieback and stem cankers on plum in Turkey - Ören, Emel; Palacıoğlu, Gülsüm; Ozan, Gülten Nisan; Bayraktar, Harun (SPRINGER, 2022)
Plum (Prunus domestica) is an economically important fruit tree in Turkey. In the summer of 2021, canker symptoms were observed on the plum trees in an orchard located in Adıyaman province, Turkey, with an incidence of approximately 4%. Symptoms included branch dieback, gummosis, dark vascular discoloration, and stem canker. Samples of diseased tissues were collected, surface-sterilized with 1% sodium hypochlorite for 2 min and plated onto potato dextrose agar containing 0.5 g L−1 streptomycin sulfate. The plates were incubated for 10 days at 23 °C in dark. Arthroconidia produced on aerial mycelium as arthric chains were dark brown, thick-walled, disarticulating, cylindrical to oblong, 0 to 1 septate, 9.25–4.37×4.27–2.96 μm (n=30). Pycniospores occurring on pine needles were hyaline, ellipsoidal to oval, 0–1 septate, 3.5–4.5×10.5–13.2 μm (n=30)
Keywords: Neoscytalidium novaehollandiae; Plum; Dieback and canker